Penerapan E-Government Dalam Meningkatkan Infrastruktur Jalan Di Kabupaten Probolinggo Melalui Aplikasi Sistem Informasi Perbaikan Jalan Rusak Bersama Masyarakat (Si Prenjak Emas) - Triowijaya, Moch (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to describe the implementation of the Si Prenjak Emas application as a form of e-government implementation to support road infrastructure improvements in Probolinggo Regency. The background to this research is based on the high rate of road damage that exceeds the funding capacity of the Regional Budget (APBD), as well as the public's lack of understanding regarding road authority and class. The research method used is descriptive qualitative, with data collection techniques through interviews and documentation. The results indicate that the implementation of Si Prenjak Emas has successfully increased the efficiency and effectiveness of public services in the road infrastructure sector.